2019
DOI: 10.3389/fphar.2019.01312
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Ethanol Exposure Misregulates Genes Involved in Iron Homeostasis Promoting a Maladaptation of Iron Dependent Hippocampal Synaptic Transmission and Plasticity

Abstract: Prenatal ethanol exposure (PAE) induces behavioral maladptations in offspring, including a deficit in memory formation which is part of the umbrella sign of fetal alcohol spectrum disorder. Clinical and preclinical studies have shown that iron depletion exacerbates cognitive problems in offspring exposed to ethanol in utero and that PAE promotes dysregulation in brain iron homeostasis. However, the mechanisms underlying brain iron dysregulation and neuronal activity defects in adolescent offspring of PAE are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“… 4 A previous study has reported that excessive iron treatment directly leads to LTP by an electrophysiological approach. 53 Intrahippocampal iron causes toxic effects and cognitive dysfunction manifested by the damage of dendritic structure and downregulation of synapse-related proteins, including BDNF, SYP, PSD95, and tenascin C. 54 At the same time, excess iron could accelerate mitochondrial oxidative damage caused by CIH. 16 , 34 …”
Section: Discussionmentioning
confidence: 99%
“… 4 A previous study has reported that excessive iron treatment directly leads to LTP by an electrophysiological approach. 53 Intrahippocampal iron causes toxic effects and cognitive dysfunction manifested by the damage of dendritic structure and downregulation of synapse-related proteins, including BDNF, SYP, PSD95, and tenascin C. 54 At the same time, excess iron could accelerate mitochondrial oxidative damage caused by CIH. 16 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Neuronal iron accumulation is indispensable for the functional plasticity of excitatory glutaminergic synapses [ 15 , 30 , 31 ]. The tight interaction between neuroinflammation and iron overload has been revealed in several pathological conditions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of prenatal alcohol exposure on glial cells, including radial glia and other transient glial structures present in the developing brain, astrocytes, oligodendrocytes and their precursors and microglia contribute to abnormal neuronal development, reduced neuron survival and disrupted brain architecture and connectivity (24). In addition, prenatal alcohol exposure affects iron homeostasis of specific brain areas (prefrontal cortex [PFC]) and the hippocampus, which could be involved in maladaptive cognition (25). Also, past and recent patterns of intermittent heavy alcohol consumption are associated with reduced frontal cortical thickness (i.e.…”
Section: Impact On the Brainmentioning
confidence: 99%